Penser l`intégration et l`éducation par le sport en France : réflexions sur les catégories d`analyse sociale et politique - Gasparini, W. (Movement & Sport Sciences - Science & Motricité, 2012)
This article examines "integration" and "education through sport" as categories of analysis and thought (Brubaker, 2001). In France, apart from sport practice in the school athletic associations, education through sport is outside the field of compulsory physical education. It is placed in the field of voluntary sport actvity and particularly in the initiative of the sports movement. However, unlike other European countries, in France the notion of education through sport is not really used. It is generally prefered the concepts of integration or inclusion through sport. The article proposes to examine the consensus of social functions of sport as "naturally" integrator and to show that freedom, regarding national categories of thought, cannot be conquered without an effort to make explicit the problems related to the educational and civic virtues of sport.